2008
DOI: 10.1017/s1460396908006377
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and supporting body image and sexual concerns for young women with breast cancer: a literature review

Abstract: Background: Breast cancer is the most common cancer and most common cancer cause of death in women aged 20À49 years in Canada. Developing a functional definition of 'young' is imperative in assessing and providing appropriate emotional support to the unique body image and sexuality concerns facing 'young' women with breast cancer. These concerns require proper assessment in order to provide appropriate interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(207 reference statements)
0
2
0
1
Order By: Relevance
“…Their views are consistent with studies that indicate that the psychosocial effect of cancer in younger people (Zebrack, 2011) and the long-term impact of cancer treatment on the quality of life of younger women (Geue et al, 2014) is not represented adequately in research. Addressing the effects of the latter has been identified as essential to improving the quality of life of young women with breast cancer (Fobair et al, 2006), particularly in a population where the impact of treatment expands over decades (Gilbert, Ussher, & Perz, 2010;Kinamore, 2008). In addition, researchers identified that, even when information is available, a need exists to develop mechanisms that allow the information to reach relevant patient groups (National Institute for Health and Care Excellence, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their views are consistent with studies that indicate that the psychosocial effect of cancer in younger people (Zebrack, 2011) and the long-term impact of cancer treatment on the quality of life of younger women (Geue et al, 2014) is not represented adequately in research. Addressing the effects of the latter has been identified as essential to improving the quality of life of young women with breast cancer (Fobair et al, 2006), particularly in a population where the impact of treatment expands over decades (Gilbert, Ussher, & Perz, 2010;Kinamore, 2008). In addition, researchers identified that, even when information is available, a need exists to develop mechanisms that allow the information to reach relevant patient groups (National Institute for Health and Care Excellence, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another key issue examined concerns the effects of mastectomy on women's sexual life. Many women with a mastectomy feel less desirable and exhibit reduced self-confidence in sexual behavior (Ashing-Giwa et al, 2004;Crouch & McKenzie, 2000;Landmark & Wahl, 2002) and this is true, especially for younger women (Avis et al, 2004;Fobair et al, 2006;Hill & White, 2008;Kinamore, 2008;Thewes et al, 2004). Long-lasting changes in women's sexual mood, arousal, and satisfaction, as well as a reduction in the frequency of sexual contact, have been reported (Ussher et al, 2012(Ussher et al, , 2014.…”
Section: The Psychosocial Impact Of Mastectomymentioning
confidence: 99%
“…Αρκετές έρευνες έχουν διερευνήσει την επίδραση του καρκίνου του μαστού γενικότερα και της μαστεκτομής ειδικότερα στη σεξουαλικότητα των γυναικών, κάτι που φαίνεται ότι αποτελεί πρόβλημα κυρίως για τις νεότερες γυναίκες (Hill, & White, 2008. Kinamore, 2008.…”
Section: οι ψυχοκοινωνικές συνέπειες της μαστεκτομήςunclassified